PENGARUH TEPUNG DAUN CENGKEH TERHADAP PERTUMBUHAN DAN HASIL TOMAT ORGANIK - Evita . (Bioplantae, 2012)
The aimed of this research to exmaine of the effect of colve leaves powder on the growth and yield of organik tomatoes. This research was cunducted in Randomized block design, with five treatments of cinnamon powder dosage and four replication. The cinnamon powder dosage are, c0 = 0.0 g plot-1 , c1 = 250.0 g plot-1, c2 = 500.0 g plot-1 , c3 = 750.0 g plot-1, c4 = 1000.0 g plot-1 . The parameters observed are plant height, time of flowering and fruitset, root dried weight, plant dried weight and plant yield. The result showed that, there no signicantly differences between treatment on growth parameter. The significantly effect only achived on yield component. The highest tomatoes yield and the number of tomatoes was achieved at dosages 500.0 g plot-1colve leaves powder Key words : Leaves powder, tomato, organic